2019
DOI: 10.1039/c8na00396c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic control of a galvanic replacement reaction on cuprous oxide

Abstract: The galvanic replacement (GR) reaction of Au on Cu2O is mediated by the disproportionation of the substrate. As a result, the morphology of the deposited film can be controlled by the chemical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It is driven by the difference in reduction potentials between the surface metal atoms and the cations in solution, resulting in oxidation of the surface atom via reduction of the cation to its neutral state. As such, the process is sensitive to the chemistry of the metallic species at the surface and the cation in solution . Galvanic replacement demonstrates a flexible design approach in which the morphology and electronic composition of the active sites of the TMNP can be finely and independently tuned. Equation summarizes the overall reaction occurring at the surface sites: The process effectively replaces n surface atoms of metal M2 with m atoms of metal M3, resulting in an M1M2@M1M3 pseudo-core@shell structure.…”
Section: Preparation Of Trimetallic Catalystsmentioning
confidence: 99%
“…It is driven by the difference in reduction potentials between the surface metal atoms and the cations in solution, resulting in oxidation of the surface atom via reduction of the cation to its neutral state. As such, the process is sensitive to the chemistry of the metallic species at the surface and the cation in solution . Galvanic replacement demonstrates a flexible design approach in which the morphology and electronic composition of the active sites of the TMNP can be finely and independently tuned. Equation summarizes the overall reaction occurring at the surface sites: The process effectively replaces n surface atoms of metal M2 with m atoms of metal M3, resulting in an M1M2@M1M3 pseudo-core@shell structure.…”
Section: Preparation Of Trimetallic Catalystsmentioning
confidence: 99%
“…The experimental results revealed that the GRR mechanism in the metal oxide is based on redox couple reactions between multivalent metallic ions, replacing the ions with a higher oxidation state in the templates with metal ions of a lower oxidation state from the solution. This strategy has been further developed to synthesize oxide/metal heteronanostructures 85 . The experimental and theoretical studies revealed that the cost‐effective transition metal oxides (CuO x , FeO x , and MnO 2 ) could react with Pt due to their higher galvanic potential than Pt 4+ and Rh 3+ 86–88 .…”
Section: Grr In the Unconventional Nanoparticle Systemsmentioning
confidence: 99%
“…22 Aqueous solutions of lactate-stabilized Cu 2+ at high pH (9)(10)(11)(12) are used for the electrodeposition of Cu2O in the narrow range of electrode potentials noted by the Pourbaix diagram. [23][24][25][26] The Pourbaix diagram also suggests that metallic copper can be deposited at more negative potentials in the same alkaline conditions. Therefore, the electrodeposition of copper in dendritic morphologies is possible at sufficiently negative potentials while mitigating the morphological consequences of DHBT.…”
mentioning
confidence: 92%